BIOPROSPEKSI BAKTERI YANG BERASOSIASI DENGAN ALGA HIJAU HALIMEDA MACROLOBA, CAULERPA RACEMOSA, DAN ULVA SP SEBAGAI PENGHASIL SENYAWA ANTIBAKTERI - Risky Panji Nugroho; Anto Budiharjo; Endang Kusdiyantini (Jurnal Akademika Biologi, 2013)
Bacteria can grow in various environments, including those associated with marine organisms such as algae, sponge, sea grass and soft corals. For these organisms, bacteria help building their defense by producing secondary metabolites such as bioactive compound.  This research aims to study the potency of the bacteria which interact with green algae Halimeda macroloba, Caulerpa racemosa, and Ulva sp which are able to produce antibacterial compound. Algae, which belong to Chlorophyta, are common to be found in marine water. This research used bacterial isolation, morphologic bacterial isolate characterization, antibacterial test, molecular identification of the antibacterial compound producer isolate, and biochemical activity test. From the isolation, the researcher was able to collect five bacterial isolate; one from H. macroloba, three from C. racemosa, and one isolate from Ulva sp. Of the five isolates, one isolate from C. racemosa can prevent the E.coli, and one isolate from H. macroloba can prevent E.coli and P.aeruginosa. Isolate derived from Halimeda macroloba have the biggest prevention zone ability, which is 18.1 mm, towards P.aeruginosa. Keywords: Antibacterial, Bacterial Association, Halimeda macroloba, Caulerpa racemosa,      Ulva sp